Evaluating the performance of efficient Cu2NiSnS4 solar cell—A two stage theoretical attempt and comparison to experiments - Most. Marzia Khatun; Adnan Hosen; Sheikh Rashel Al Ahmed (Heliyon, 2023)
In this work, copper nickel tin sulfide (Cu2NiSnS4) as an encouraging alternative absorber for thin-film photovoltaic devices is explored. Here, the Cu2NiSnS4 (CNTS) absorber-based heterojunction solar cell is designed through a two-stage theoretical approach using Solar Cell Capacitance Simulator in one-dimension (SCAPS-1D). Initially four different hole transport materials (MoO3, SnS, NiOx, and PEDOT.PSS) are incorporated at the back interface in experimentally configured Au/Cu2NiSnS4/ZnS/ZnO/ITO cell to boost the device outputs. The MoO3 semiconductor is anticipated as a hole transport layer (HTL) in the heterojunction Ni/MoO3/Cu2NiSnS4/ZnS/ZnO/ITO solar configuration. It is revealed that an appropriate band alignment can be formed at MoO3/Cu2NiSnS4 interface with less interfacial defects among other HTLs with CNTS absorber, thus improving the solar cell outputs. Efficiency is increased from 2.71% to 8.79% for the proposed CNTS-based solar cell. Further optimization is accomplished concerning thickness, defect states, and doping density of the various materials utilized in the heterojunction structure. Defect characteristics at the MoO3/Cu2NiSnS4 and Cu2NiSnS4/ZnS interfaces are also evaluated and optimized to boost the conversion efficiency significantly. Moreover, the effects of operating temperature and rear electrode work function on the outputs of the designed solar device are studied. The aforesaid two-stage optimization yields efficiency of 12.46% with VOC of 1.23 V, JSC of 12.66 mA/cm2, and FF of 79.78%. Therefore, these findings will facilitate the scientific communities to further progress an economical and extremely efficient CNTS-based solar device with a promising MoO3 HTL.